Deontología del Ministro de la Penitencia. Sigilo sacramental y secreto penitencial - Etxeberría Sagastume, Juan José (Estudios eclesiásticos, 2010)
The sacramental seal and penitential secret are two key issues concerning the deontology of the ministry of penitence. Its nature, matter, foundation and relation with other canons of Canon Law lead to understand the reason why the Church, through legal channels, is concerned about conserving and defending them under full compromise. From the canons analyzed, it can be seen that the sacramental seal is inviolable as well as being permanent and everlasting. Nobody, except the penitent, can authorize a priest to reveal what he has heard in confession under sacramental absolution. For this reason, the maximum protection of the confidential relation between the priest and the faithful is defended under confessional laws, and not only by the Catholic Church. Moreover, the violation of both the seal and the secret are crimes with a canonical sanction, and which will be imposed in accordance to the seriousness of the crime committed.